2022
DOI: 10.1155/2022/9154295
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Oxidative Stress Tethered to Cardiovascular Diseases

Abstract: Cardiovascular disease (CVD) is a broad term that incorporated a group of conditions that affect the blood vessels and the heart. CVD is a foremost cause of fatalities around the world. Multiple pathophysiological mechanisms are involved in CVD; however, oxidative stress plays a vital role in generating reactive oxygen species (ROS). Oxidative stress occurs when the concentration of oxidants exceeds the potency of antioxidants within the body while producing reactive nitrogen species (RNS). ROS generated by ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 174 publications
1
29
0
Order By: Relevance
“…Besides ROI, reactive nitrogen species (RNS) are involved in tissue destruction, forming nitrotyrosine, a product of tyrosine nitration mediated by reactive nitrogen species such as peroxynitrite anion and nitrogen dioxide. Nitrotyrosine is identified as an indicator or marker of cell damage, inflammation, and NO (nitric oxide) production [49].…”
Section: Discussionmentioning
confidence: 99%
“…Besides ROI, reactive nitrogen species (RNS) are involved in tissue destruction, forming nitrotyrosine, a product of tyrosine nitration mediated by reactive nitrogen species such as peroxynitrite anion and nitrogen dioxide. Nitrotyrosine is identified as an indicator or marker of cell damage, inflammation, and NO (nitric oxide) production [49].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous methods and assays that may be used to determine the status of the OxS biomarkers in a range of biological samples, which is a major advantage but also a downside. Each method has its own set of pros and limitations, as well as practicality and economic considerations [158]. The interpretation of data may also be complicated by a number of pre-and post-analytical difficulties, which require further standardization such as preanalytical issues, analytical issues and, postanalytical issues [159].…”
Section: Neuroprotection: Challenges and Opportunitiesmentioning
confidence: 99%
“…However, excess ROS can cause redox imbalance, resulting in myocardial cell apoptosis and necrosis, fibroblast proliferation, activation of matrix metalloproteinases (MMPs), collagen deposition, and other pathophysiological processes, activating oxidative stress and causing pathological myocardial remodeling, leading to various diseases, such as myocardial infarction, hypertension, arrhythmia, heart failure, and vascular dysfunction ( 21 23 ). Excessive production of ROS also activates a variety of hypertrophic signaling kinases and transcription factors, disrupting the contractile function of excitation-contraction coupling core proteins, causing mitochondrial DNA(mtDNA) damage, lipid and protein peroxidation, abnormal ion channel function, leading to fibroblast proliferation, vascular endothelial dysfunction, interstitial fibrosis, atheromatous plaque formation, thromboembolism formation and inadequate cardiac energy supply, eventually progressing to heart failure ( 24 28 ). Recent studies have shown that ROS produced by mitochondria activate the oxidative stress process, causing apoptosis and interstitial fibrosis, resulting in functional and structural impairment, leading to deterioration of right ventricular (RV) function and pressure overload, which in turn leads to right heart failure ( 29 ).…”
Section: Nicotinamide Adenine Dinucleotide Phosphate Oxidasementioning
confidence: 99%